Making the invisible visible: bioelectrical impedance analysis demonstrates unfavourable body composition in rheumatoid arthritis patients in clinical practice. (August 2014) - Konijn, NPC; van Tuyl, LHD; Bultink, IEM; Lems, WF; Earthman, CP; van Bokhorst-de van der Schueren, MAE
<x xml:space="preserve">Abstract</x> Objectives: To examine differences between the assessment of body composition by body mass index (BMI) and bioelectrical impedance analysis (BIA) in patients with rheumatoid arthritis (RA). Method: The body composition of RA patients was assessed during their visit to the outpatient department of a Dutch academic hospital using BMI, fat-free mass index (FFMI), and fat mass index (FMI). FFMI and FMI were determined by single-frequency BIA. Results: Sixty-five consecutive RA patients (83% women, mean age 58 years, median disease duration 7 years) with moderately active disease [mean Disease Activity Score using 28 joint counts (DAS28) = 3.40; mean Rheumatoid Arthritis Disease Activity Index (RADAI) score = 3.49] and moderate disability [mean Health Assessment Questionnaire (HAQ) score = 0.87] were included. Based on BMI, 2% of our study population were underweight, 45% had a healthy body composition, and 54% were overweight or obese. Based on BIA, 18% of the patients showed a low FFMI and 74% had a high or very high FMI. Low FFMI was found in 44% of the women with a normal BMI, and high FMI was found in 40% of the women and 75% of the men with a normal BMI. Conclusions: A high frequency of unfavourable body composition, predominantly reduced FFMI and elevated FMI, was found in a cohort of RA patients with moderately active disease, turning BMI into an unreliable method for assessment of body composition in RA. BIA, however, might be the preferred method to assess FFMI and FMI in RA patients in clinical practice, as it is easy to use and relatively inexpensive.